2019
DOI: 10.1080/21606544.2019.1623083
|View full text |Cite
|
Sign up to set email alerts
|

Economic valuation of ecosystem goods and services: a review for decision makers

Abstract: This is a repository copy of Economic valuation of ecosystem goods and services: a review for decision makers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 137 publications
(100 reference statements)
0
15
0
2
Order By: Relevance
“…Uncovering the perceptions of cultural ESs by the different actors needs participatory approaches, as consultative methods (e.g., questionnaire) or group-based methods (focus groups) [51]. Furthermore, the economic valuation of the ESs, although subject to debate and criticism [56], is of growing interest to analyze the individuals' perception of cultural ESs [28]. The choice experiment or contingent valuation are for example common methods [2,30,31,57].…”
Section: Discussionmentioning
confidence: 99%
“…Uncovering the perceptions of cultural ESs by the different actors needs participatory approaches, as consultative methods (e.g., questionnaire) or group-based methods (focus groups) [51]. Furthermore, the economic valuation of the ESs, although subject to debate and criticism [56], is of growing interest to analyze the individuals' perception of cultural ESs [28]. The choice experiment or contingent valuation are for example common methods [2,30,31,57].…”
Section: Discussionmentioning
confidence: 99%
“…These efforts have complemented scholarly debates concerning how to recognise the importance of different kinds of values in decision-making (for an overview, see: Arias-Arévalo et al 2017). The division of instrumental benefits of the environment into use and non-use (or passive-use) values is well-established (Arrow et al 1993;Carson et al 2001;Tinch et al 2019). In parallel, philosophical arguments have been made about the structure of the worth of nature in-and for itself, building on the long tradition of studying intrinsic values in environmental ethics (Rolston 1988;Callicott 1992;O'Neill 1992;Muraca 2011;Davidson 2013;Batavia and Nelson 2017;Piccolo 2017;O'Connor and Kenter 2019).…”
Section: Theoretical Traditions In Social Values For Sustainabilitymentioning
confidence: 99%
“…The recent use of natural capital (NC) and natural capital accounting methodology in UK government environment plans (see Curnow, 2019) has shown the potential applications of the NC approach in environmental project and policy appraisal, and regulation, including water and asset management planning by water companies. The applicability of this methodology to valuing ecosystem services has been reviewed by Tinch et al (2019); whilst Davis et al (2019) demonstrated the use of this methodology to appraise the value of improvements to water quality needed to establish new salt marshes as a means of realigning coastal sea defences. Some water companies are adopting an ecosystem resilience and natural capital approach to managing their water catchment areas, as a way of improving water supply and water quality delivery (see United Utilities Water 2018), including reducing discolouration, reducing water pollutants, and improving waste water discharges into the environment.…”
Section: Methodological Investigationsmentioning
confidence: 99%